2011
DOI: 10.1007/s11104-011-0742-x
|View full text |Cite
|
Sign up to set email alerts
|

Retranslocation of nutrients in relation to boron availability during leaf senescence of Betula pendula Roth

Abstract: Boron (B) is an essential micronutrient, whose deficiency is common in boreal forests. Our aim was to investigate the effects of the B supply on the retranslocation of micro-and macro nutrients in seedlings of Betula pendula Roth. One-year-old seedlings were grown under three different levels of B: 0%, 30% and 100% of the standard level for complete nutrient solution. Half of the seedlings were harvested after summer period and another half when leaves abscised. Boron was not resorbed in significant amounts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Efficient removal of K and P has been observed from A. thaliana leaves (Himelblau and Amasino, 2001 ; Waters and Grusak, 2008 ) and also from senescing leaves of deciduous trees (Hagen-Thorn et al, 2006 ). In contrast, Teija Ruuhola ( 2011 ) found that K concentrations increased significantly throughout the entire leaf live span in Betula pendula while Harvey and van den Driessche ( 1999 ) observed a differential remobilization of P and K from P. nigra leaves depending on drought status (Harvey and van den Driessche, 1999 ; Teija Ruuhola, 2011 ). It has been strongly suggested that remobilization of P is induced by P availability.…”
Section: Discussionmentioning
confidence: 97%
“…Efficient removal of K and P has been observed from A. thaliana leaves (Himelblau and Amasino, 2001 ; Waters and Grusak, 2008 ) and also from senescing leaves of deciduous trees (Hagen-Thorn et al, 2006 ). In contrast, Teija Ruuhola ( 2011 ) found that K concentrations increased significantly throughout the entire leaf live span in Betula pendula while Harvey and van den Driessche ( 1999 ) observed a differential remobilization of P and K from P. nigra leaves depending on drought status (Harvey and van den Driessche, 1999 ; Teija Ruuhola, 2011 ). It has been strongly suggested that remobilization of P is induced by P availability.…”
Section: Discussionmentioning
confidence: 97%
“…This could be attributed to the inefficiency of the higher Si concentrations on the nutrient balance, which may affect plant growth and leaf area [59,60]. Results also indicated that the main effect of seasons was a significant increase in leaf area from one season to another; this may be due to the accumulation of Zn and Si NPs in plant tissue after the subsequent spray of the NPs [61]. The control showed a reduction in leaf area for the 2018 "on year" in comparison to the 2017 "off year"; this may be due to the competition between fruit growth and vegetative growth during the "on year" [62].…”
Section: Leaf Areamentioning
confidence: 99%
“…Populations at different latitudes differ in their response to environmental cues, most notably to photoperiod, suggesting selection pressure on autumnal phe-nology. Such differentiation has been described for phenological events such as growth cessation (Soolanayakanahally et al, 2013), bud set (Ingvarsson et al, 2006;Friedman et al, 2011;Soolanayakanahally et al, 2013), leaf senescence (Pudas et al, 2008;Fracheboud et al, 2009;Friedman et al, 2011;Soolanayakanahally et al, 2013), cold hardiness (Friedman et al, 2011), and dormancy (Ruuhola et al, 2011).…”
Section: Getting Ready For Overwinteringmentioning
confidence: 99%